Marital Conflict Behaviors and Implications for Divorce over 16 Years - Birditt, Kira S. (2010)
This study examined self-reported marital conflict behaviors and their implications for divorce. Husbands and wives (N = 373 couples; 47% White American, 53% Black American) reported conflict behaviors in years 1, 3, 7, and 16 of their marriages. Individual behaviors (e.g., destructive behaviors) and patterns of behaviors between partners (e.g., withdrawal-constructive) in Year 1 predicted higher divorce rates. Wives’ destructive and withdrawal behaviors decreased over time, whereas husbands’ conflict behaviors remained stable. Husbands reported more constructive and less destructive behaviors than wives and Black American couples reported more withdrawal than White American couples. Findings support behavioral theories of marriage demonstrating that conflict behaviors predict divorce and accommodation theories indicating that conflict behaviors become less negative over time.